Kyai Leadership in Multicultural Dakwah of Majlis Zikir Manaqib Syekh Abdul Qadir Jailani at Al Qodiri Islamic Boarding School in Gebang Jember - Abdul Muis (Jurnal Al-Hikmah, 2023)
Islam, which initially emerged in Mecca and migrated to Medina, has undergone a significant development until the passing of Prophet Muhammad. During the time of the companions, Islam's development was not only in the Arabian Peninsula but had spread to various corners of the country. This study focuses on the leadership of kyai (Islamic scholars), models, materials, methods, and the role of multicultural da'wah, with the aim of describing the leadership of kyai, models, materials, methods, and the role of multicultural da'wah. This research uses a descriptive qualitative approach. The results of this study show that the kyai plays a central role in multicultural da'wah in the majlis zikir manaqib. The model of multicultural da'wah in the majlis zikir manaqib at the Al-Qodiri Islamic boarding school is in the form of halaqah (study circle), intensive studies, general lectures, istighasah (supplication), and taklim (religious lesson). Meanwhile, the material covers issues of welfare, humanity, amar ma'ruf nahi munkar (enjoining what is good and forbidding what is evil), social justice, democracy, human rights, education and liberation, as well as multicultural themes sourced from the Qur'an and Hadith and current issues that emphasize aspects of inner awareness and self-creativity. The method used is a synergistic collaboration between oral, written, and, most importantly, practical aspects that are dynamic, communicative, and familiar. Meanwhile, the role of multicultural da'wah is to contribute to the process of empowering the congregation from the problems of ignorance, underdevelopment, and various issues of distress experienced by them.